2003
DOI: 10.1080/01140671.2003.9514250
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fruiting cane origin on fruitfulness of hardy kiwifruit,Actinidia arguta

Abstract: Morphology of Actinidia arguta 'Ananasnaya' vines was studied at two sites in Oregon, United States in 1998 and at one site in 1999. One-year-old fruiting wood was divided into five types/origins: spurs borne from the cordon; 1-year-old canes from the cordon; 1-year-old canes which grew as a result of summer pruning of last year's growth (1-year-old tipped); 1-year-old canes borne from 2-year-old wood; and 1-year-old canes borne from 3-year-old wood. Wood type had no effect on percent fruitful shoots or the nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…Shading after harvest, however, had no significant effect on the number of flowers per shoot or flower cluster position. The position of flowers on shoots in unshaded vines was consistent with earlier reports (Tiyayon & Strik, 2003). Shading in 1998 had no effect on flowers or clusters per shoot originating from spurs in 1999 (data not shown).…”
Section: Effect Of Shading On Subsequent Floweringsupporting
confidence: 90%
“…Shading after harvest, however, had no significant effect on the number of flowers per shoot or flower cluster position. The position of flowers on shoots in unshaded vines was consistent with earlier reports (Tiyayon & Strik, 2003). Shading in 1998 had no effect on flowers or clusters per shoot originating from spurs in 1999 (data not shown).…”
Section: Effect Of Shading On Subsequent Floweringsupporting
confidence: 90%
“…In contrast to the finding that wood age did not affect shoot length, diameter, internode length, and fruit number per shoot in kiwifruit (Tiyayon and Strik 2010), wood age at the point of cutting in olive trees strongly influenced shoot type and its vigor in subsequent growing seasons (Fig. 3).…”
Section: Discussionmentioning
confidence: 63%
“…Although practical field experience in many fruit trees suggests that shoot elongation often increases with wood age at the cutting points, a few studies have experimentally evaluated the effect of wood age on shoot demography and reproductive characteristics (Lauri et al 1996;Tiyayon and Strik 2010;Stanley 2016). Interestingly, experimental evidence in kiwifruit found that neither shoot length nor fruit number differed with wood age after summer pruning (Tiyayon and Strik 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation